PENTINGNYA AKREDITASI DALAM PROSES PEMBINAAN MANAJEMEN SEKOLAH/MADRASAH DI SUMATRA UTARA - Dyah Suryawati (Widyariset, 2010)
Accreditation is one of the important activities in education and became one of the indicators of accountabilityin education. Quality of education in Indonesia is still left behind and the disparity of school quality in Indonesia isstill high, particularly among school that are on the island of Java and outside Java island. Based on these need tobe inspected the implementation and barriers or obstacle faced in the implementation of the accreditation school/madrasah at these time. This research is expected to improve the quality of the implementation of accreditation sothat the trust stakeholders with the implementation of the accreditation of school/madrasah increase. The approachused in this research is a qualitative approach. Based on the data, the results of accreditation have not been fullyused as basic guidance the school/madrasah by the related institution.